ANTITUSSIVE PHARMACOTHERAPY IN ACUTE COUGH: EFFICACY, SAFETY, AND CURRENT CLINICAL EVIDENCE - Aleksandra Grygorowicz; Klaudia Baran; Michał Ględa; Michał Szyszka; Weronika Radecka; Weronika Kozak; Agnieszka Szreiber; Karol Grela; Karolina Nowacka; Kamil Jabłoński; Anna Woźniak (International Journal of Innovative Technologies in Social Science, 2025)
Background: Acute viral cough is one of the most frequent reasons for primary-care consultation, yet evidence for commonly used antitussive agents varies widely. This review synthesizes current data on the pathophysiology, efficacy, safety, and clinical recommendations guiding antitussive pharmacotherapy. Methods: This review synthesizes current evidence on antitussive pharmacotherapy in acute cough in adults and children. A narrative review of eligible publications indexed in PubMed, Scopus, and Google Scholar from 2013–2025 was conducted, prioritizing systematic reviews, randomized controlled trials, pharmacovigilance studies, and clinical guidelines. Search terms included “acute cough”, “antitussive”, “dextromethorphan”, “codeine”, “hydrocodone”, “levodropropizine”, “butamirate”, “benzonatate”, “ivy leaf”, “Pelargonium sidoides”, and “honey”. Relevant studies were screened and qualitatively analyzed. Results: Acute viral cough arises from inflammatory sensitization of airway sensory pathways and heightened brainstem cough-reflex responsiveness. Opioid antitussives demonstrate limited symptomatic benefit and present substantial safety concerns, particularly in pediatric populations. Centrally acting non-opioid agents, such as dextromethorphan, show modest and inconsistent efficacy with dose-dependent toxicity. Peripherally acting antitussives—notably levodropropizine—exhibit more consistent reductions in cough severity with favorable tolerability. Complementary agents, including ivy leaf extract, Pelargonium sidoides, and honey in children over one year, offer modest symptomatic benefit with strong safety profiles. Contemporary guidelines consistently discourage routine antitussive use and emphasize the self-limiting nature of acute viral cough. Conclusion: Evidence supports a cautious, symptom-targeted approach to pharmacologic therapy in acute viral cough, prioritizing safety and reserving antitussives for selected clinical scenarios.